Switching mechanism in two-terminal vanadium dioxide devices. (27th March 2015) - Radu, Iuliana P; Govoreanu, B; Mertens, S; Shi, X; Cantoro, M; Schaekers, M; Jurczak, M; De Gendt, S; Stesmans, A; Kittl, J A; Heyns, M; Martens, K
Abstract: Two-terminal thin film VO2 devices show an abrupt decrease of resistance when the current or voltage applied exceeds a threshold value. This phenomenon is often described as a field-induced metal–insulator transition. We fabricate nano-scale devices with different electrode separations down to 100 nm and study how the dc switching voltage and current depend on device size and temperature. Our observations are consistent with a Joule heating mechanism governing the switching. Pulsed measurements show a switching time to the high resistance state of the order of one hundred nanoseconds, consistent with heat dissipation time. In spite of the Joule heating mechanism which is expected to induce device degradation, devices can be switched for more than 10 10 cycles making VO2 a promising material for nanoelectronic applications.